Employee Performance Model Based on e-HRM: Employee Green Behavior as A Performance Indicator in The Coal Mining Company - Priyo Hadi Susananto; Muhtosim Arief; Bahtiar Usman; Tiarapuspa Tiarapuspa (Syntax Corporation Indonesia, 2023)
This paper provides a perspective on the concept of employee performance based on e-HRM in the coal mining service industry in Indonesia. The research methodology uses documentary analysis of empirical studies and examines the perceptions of managers working in the HRM field. e-HRM is human resources management that is supported by digital technology, while employee performance in this case is the performance of employees who work in coal mining companies. This study aims to identify e-HRM practices to improve employee performance in terms of green employee behavior in the workplace. The results show that employee performance is closely related to e-HRM, green employee motivation, and person-job fit. Dynamic business conditions are a challenge for companies to be able to achieve productivity, and efficiency and always pay attention to the impact of safety, health & environment (SHE). HRD Department must provide support and develop appropriate competencies for its employees to improve employee professionalism. Managers must also be adept at empowering employees, caring about employee welfare, and maintaining employee safety & health. This empirical study and interview of respondents are very necessary for companies that are trying to carry out digital transformation in the HRM field to build production performance and employee awareness of the conditions of the work environment.